Sosialisasi dan Pengenalan Computational Thinking kepada Guru pada Program Gerakan Pandai oleh Bebras Biro Universitas Bumigora - Kartarina Kartarina; Miftahul Madani; Diah Supatmiwati; Regina Aprilia Riberu; Indah Puji Lestari (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Currently school teachers, especially in Mataram City, West Lombok Regency, Central Lombok and East Lombok are not familiar with learning with the concept of computational thinking (Computational Thinking) so they cannot teach their students how to think computationally as an approach to solving existing problems. Considering one of the demands of the industrial revolution 4.0, where problem solving skills are one of the abilities that students must have. In this case, these abilities need to be taught by teachers at school. Therefore, this problem must be solved immediately by increasing the ability of teachers in learning computational thinking so that teachers can apply computational thinking learning methods to their students. From the problems listed, it is necessary to approach how to train teachers to teach computationally thinking to their students. In Lombok, West Nusa Tenggara, to apply Computational Thinking (CT) in formulating problems and revealing solutions, namely through socialization and training and mentoring of free computational thinking materials to teachers in schools in Lombok, NTB which was held in the form of CT Bebras socialization activities, which is expected to help introduce and apply Computational Thinking (CT) material as a creative learning method in schools in NTB.